Trichinellosis in Serbia has become a rare event - one outbreak with pulmonary complications - Mitic, Ivana; Vasilev, Sasa; Korac, Milos; Ilic, Natasa; Bojic, Biljana; Gruden-Movsesijan, Alisa; Sofronic-Milosavljevic, Ljiljana (Folia parasitologica, 2022)
An outbreak of trichinellosis occurred in Stari Banovci, a settlement in the municipality of Stara Pazova, Srem, Republic of Serbia, in March-April 2019. A total of 28 persons were exposed and trichinellosis was confirmed in 24 of them. This outbreak involved members of eight families, their relatives and friends. The infection, due to Trichinella spiralis (Owen, 1835), was associated with consumption of pork sausages procured in a local butcher's shop. The trace-back study revealed that the meat originated from swine that was raised on a small farm belonging to the owner of the shop, who did not have permission from the Veterinary Directorate for slaughtering animals and who put on the market sausages prepared from uninspected meat. Trichinellosis was accompanied by typical clinical symptoms. However, the unusual occurrence of high percentage of pulmonary complications was noticed. The description of this outbreak indicates that medical practitioners should initiate treatment immediately in cases of high suspicion of trichinellosis, even if the serology is negative, to prevent the complications of the disease. In spite of significant achievements in the control of Trichinella infection among domestic pigs and humans in the last 10 years, it is obvious that such cases of breeding animals under inappropriate conditions, slaughtering them without approval and placing uninspected pork on the market represent a source of sporadic outbreaks in Serbia.
Keywords: Trichinellosis; prasata; Swine; Serbia; Disease Outbreaks; Animals; Meat; lidé; Srbsko; maso; Humans; zvířata; trichinelóza; Trichinella spiralis; epidemický výskyt choroby